Effect of Binary Mixture of Waste Plastics on the Thermal Behavior of Pyrolysis Process - Ghosh, Ujjal; Pek, W. (John Wiley & Sons, Inc., 2015)
Waste plastic is non-biodegradable material that does not decompose naturally for a long time. The pyrolysis process is a reliable method to decompose plastic wastes, which involves breaking of the heavy carbon chains and convert to light hydrocarbons. The light hydrocarbon products can be used as fuel to power vehicles and power stations. Pyrolysis experiment was conducted using thermogravimetric analysis (TGA)/DSC equipment for different types of non-recyclable waste plastics: PET, HDPE, LDPE, PP, PS foam, and PS rigid. Investigations have been done to study the effect of binary mixture composition of PP and HDPE on pyrolysis behavior. Interactions between the plastics have been found to occur at the mixture composition range of 20–80 wt %. The decomposition rates of the individual plastics enhanced after the binary mixing of the different types of plastics. It was also found that secondary reaction occurred when mixing two types of plastics. The activation energy of the first step pyrolysis reaction is also higher than the secondary reaction. Overall, the activation energy of the pyrolysis reaction is decreased by 55% at the range of 20–80 wt % of binary mixture composition.